Measuring Equity in the Hospital Setting: An HCAHPS Application of the Health Equity Summary Score. Issue 1 (26th January 2023) - Beckett, Megan K.; Hambarsoomian, Katrin; Martino, Steven C.; Agniel, Denis; Hudson Scholle, Sarah; Maksut, Jessica L.; Mathews, Megan; Orr, Nate; Elliott, Marc N.
Abstract : Background: Health care quality varies by patient factors, including race-and-ethnicity and preferred language. Addressing inequities requires identifying them and incentivizing equity. Objectives: We apply an approach first implemented in the Medicare Advantage setting to measure equity in patient experiences by race-and-ethnicity [Asian American and Native Hawaiian or Pacific Islander (AA and NHPI), Black, Hispanic, vs. White] and language preference (English-preferring vs. another-language-preferring). We identify characteristics of hospitals providing high-quality equitable care. Research Design: We estimated, standardized, and combined performance measures into a Health Equity Summary Score (HESS) using 2016–2019 Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey data. The HCAHPS HESS considered current cross-sectional performance, within-hospital improvement, and overall improvement by race-and-ethnicity and language preference. Subjects: A total of 3333 US hospitals with 2019 HCAHPS Star Ratings. Results: The HCAHPS HESS was calculable for 44% of hospitals. High-scoring (4–5 diamonds on a 1-diamond to 5-diamond scale) hospitals tended to be smaller than intermediate-scoring [3 diamonds (14% of high-scoring hospitals had <100 beds vs. 7% of intermediate-scoring hospitals, P <0.001) and were less often for-profit (20% vs. 31%, P <0.001)]. While a significant percentage (29%) of patients served by high-scoring hospitals were AA and NHPI, Black, or Hispanic, and 9% were another-language-preferring, there were smaller proportions of Black and Hispanic patients in high-scoring versus other hospitals. HESS performance was negatively associated with the percentage of patients preferring another language to English. HESS scores were moderately correlated with overall Star Ratings ( r =0.70). Conclusions: The HCAHPS HESS and practices of high-scoring hospitals could promote more equitable patient experiences.